ETHNO- ANTHROPOLOGICAL APPROACH TO HISTORY AND CULTURE OF KUCHI TRIBES IN AFGHANISTAN - Dadman, Enayatullah; Wafiullah Aaminzai; Habibullah Haidari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The main objective of this paper is to understand the ethno- Anthropological lifestyle of Kuchi tribes of Afghanistan. Kuchi tribes is not definitively known, as their history predates written records. However, they are believed to be of Pashtun descent and have a long history in the region of Afghanistan. Kuchi tribes is deeply rooted in their nomadic lifestyle and traditional practices. They have a rich oral tradition, with storytelling and poetry playing a significant role in their culture. This paper is based on secondary data, secondary data collected through publishing and unpublished reports, newspapers, articles, journals, books and district census reports and for the analysis of these aspects we used context- analysis method. Finally, the Kuchi’s tribe of Afghanistan is in a transitional stage. They are without a doubt moving toward cutting edge values, but they did not put down their conventional values. They are not completely cut off from their conventional way of life framework and not acknowledged all the advanced of life.